Produktivitas Remote Working: Adaptasi Karyawan Terhadap Technostress dan Work Life Balance - Verni Yuliaty Ismail; Meidiati Sekarsari (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Remote working or work from home based on the HR Management function is included in the work flexibility carried out by the company to improve the quality of employee work life. In the current development of the Covid-19 Pandemic, many organizations have adopted policies to enforce remote working on employees. This study aims to determine the conditions of productivity, technostress and work-life balance of employees who do remote working and analyze the effect of technostress on work-life balance and productivity of remote working employees. This type of research is a field study designed as a survey using a questionnaire. The research population is employees who are or have been doing remote working or working from home at least 2 days a week with a total of 213 respondents. Data were analyzed using Partial Least Square-Structural Equaling Model (PLS-SEM) analysis. The results show that high levels of stress due to the use of technology while working from home can cause the balance of personal life and work-life of employees to decrease. In the end, this condition can reduce their work productivity. The readiness of employees to use technology to do remote work needs attention so that work productivity can be maintained